2020
DOI: 10.1016/s2589-7500(20)30221-1
|View full text |Cite|
|
Sign up to set email alerts
|

Chest x-ray analysis with deep learning-based software as a triage test for pulmonary tuberculosis: a prospective study of diagnostic accuracy for culture-confirmed disease

Abstract: Background Deep learning-based radiological image analysis could facilitate use of chest x-rays as triage tests for pulmonary tuberculosis in resource-limited settings. We sought to determine whether commercially available chest x-ray analysis software meet WHO recommendations for minimal sensitivity and specificity as pulmonary tuberculosis triage tests. MethodsWe recruited symptomatic adults at the Indus Hospital, Karachi, Pakistan. We compared two software, qXR version 2.0 (qXRv2) and CAD4TB version 6.0 (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 23 publications
7
88
1
Order By: Relevance
“…A prospective study was conducted in a tertiary hospital from Pakistan to evaluate the performance of qXR(v2) and CAD4TB(v6) with mycobacterial culture being a standard reference, which collected a dataset of 2187 CXRs and reported that both software achieved non-inferior accuracy (qXR: sensitivity = 0.93; specificity = 0.75; CAD4TB: sensitivity = 0.93; specificity = 0.69) to WHO-recommended minimum values, while sensitivity might be lower when smear-negative pulmonary TB was more prevalent. 27 A retrospective case–control study was conducted in a tertiary hospital from India using microbiologically-confirmed TB as the reference standard, which reported that qXR (v2) could detect TB with an AUC of 0.81, a sensitivity of 71% and a specificity of 80%. 28 As many patients who present at tertiary hospitals have symptoms suggestive of TB, accurate and rapid triage tests that can rule out the disease are needed.…”
Section: Cad With DL Technology In Tb Detectionmentioning
confidence: 99%
“…A prospective study was conducted in a tertiary hospital from Pakistan to evaluate the performance of qXR(v2) and CAD4TB(v6) with mycobacterial culture being a standard reference, which collected a dataset of 2187 CXRs and reported that both software achieved non-inferior accuracy (qXR: sensitivity = 0.93; specificity = 0.75; CAD4TB: sensitivity = 0.93; specificity = 0.69) to WHO-recommended minimum values, while sensitivity might be lower when smear-negative pulmonary TB was more prevalent. 27 A retrospective case–control study was conducted in a tertiary hospital from India using microbiologically-confirmed TB as the reference standard, which reported that qXR (v2) could detect TB with an AUC of 0.81, a sensitivity of 71% and a specificity of 80%. 28 As many patients who present at tertiary hospitals have symptoms suggestive of TB, accurate and rapid triage tests that can rule out the disease are needed.…”
Section: Cad With DL Technology In Tb Detectionmentioning
confidence: 99%
“…(6,7,15,16) Previous evaluations of CAD software have been mostly conducted in triage testing use situations, with very little data available to evaluate accuracy in community-based TB screening interventions. (6,8,16,17) Our aim was to evaluate the accuracy of the Computer-Aided Detection for Tuberculosis version 6 (CAD4TBv6) system for TB screening using a large data set (n=61,848) from the 2016 Kenya National TB prevalence survey. (18,19) To do this we used a Bayesian modelling approach to evaluate the accuracy of CAD4TBv6 and Clinical Officer CXR interpretation against the bacteriological reference standard used within the prevalence survey.…”
Section: Introductionmentioning
confidence: 99%
“…This can be used as an autonomous pre-screening tool to reduce the use of microbiological tests, Study demonstrates the impact of the software on society by performing an economic analysis Fig. 1 Six objectives that can be pursued with artificial intelligence in radiology to improve efficiency and health outcomes which are more time-consuming and costly (levels 2, 3, 6) [10][11][12][13]. This is one of the first AI applications in radiology where the software functions autonomously and has taken over the task of the radiologist.…”
Section: More Efficient Workflowmentioning
confidence: 99%